Immunoproteomic Analysis Of Mycobacterium Tuberculosis And Nontuberculous Mycobacteria Towards The Discovery Of Potential Universal Or Species Specific Biomarkers - Razman, Aimi Zafira (2017)
The immunoproteomic analysis of whole cell protein (WCP) of Mycobacterium tuberculosis complex (MTBC) and non–tuberculous mycobacteria (NTM) was carried out to identify the potential species specific and cross genus conserved species biomarkers present in the mycobacterial species. The WCP of Mycobacterium species were separated using SDS-PAGE and followed by Western blot assay to detect IgM, IgG and IgA immune response in pooled sera of TB patients and healthy subjects as well as the individual sera. The immunoreactive bands in WB assay were divided into 4 region of antigens; (1) above 67 kDa; (2) 67 kDa – 32 kDa; (3) 30 kDa, 28kDa and 26 kDa; and (4) below 25 kDa.